2015
DOI: 10.1210/me.2015-1102
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into SMAD4 Loss in Pancreatic Cancer From Inducible Restoration of TGF-β Signaling

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the fourth-leading cause of cancer death in the United States. The TGF-β signaling protein SMAD family member 4 is lost in 60% of PDAC, and this has been associated with poorer prognosis. However, the mechanisms by which SMAD4 loss promotes PDAC development are not fully understood. We expressed SMAD4 in human PDAC cell lines BxPC3 and CFPAC1 by selection of stable clones containing an inducible SMAD4 tetracycline inducible expression system construct. After 24 hours … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…When the role of TGF-β changes from tumor suppressor to tumor promoter, as reviewed in Lebrun 2012, the tumor promoting effects of TGF-β includes induction of EMT, resistance to apoptosis, migration, invasion, and tumor metastasis [ 58 ]. It has been shown that SMAD-4 deleted WT BxPC3 cells constitutively activates ERK, has an increased anti-apoptotic response but does not promote invasiveness [ 43 , 59 ]. Finally, it has also been shown that MUC1 expression can confer resistance of epithelial cancer cells to cell death via anoikis [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the role of TGF-β changes from tumor suppressor to tumor promoter, as reviewed in Lebrun 2012, the tumor promoting effects of TGF-β includes induction of EMT, resistance to apoptosis, migration, invasion, and tumor metastasis [ 58 ]. It has been shown that SMAD-4 deleted WT BxPC3 cells constitutively activates ERK, has an increased anti-apoptotic response but does not promote invasiveness [ 43 , 59 ]. Finally, it has also been shown that MUC1 expression can confer resistance of epithelial cancer cells to cell death via anoikis [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…colorectal adenocarcinoma), which occurs in about 50% of PDAC [ 2 ], appears to be of particular interest. PDAC patients carrying SMAD4 loss have a worse prognosis [ 6 , 7 ], and this event, in vitro, favors cell proliferation and migration, while antagonizing cell senescence [ 8 ]. It is widely believed that the molecular basis linking SMAD4 loss with increased tumor growth and aggressiveness depends on the absence of Smad4 protein, which mediates the effects of the transforming growth factor (TGF)-β and bone morphogenetic protein, which inhibit cell proliferation and migration, and trigger apoptosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sustained activation of signaling pathways downstream of mutant KRas then drive cancer cell survival, proliferation, migration and invasion [11]. Inactivating mutations in the tumor suppressor genes CDKN2A , TP53 and SMAD4 also promote pancreatic carcinogenesis by facilitating enhanced tumor growth and survival and are associated with poor prognosis [6,1214]. In addition to above genetic components, development of PDA is also driven by environmental factors.…”
Section: Introductionmentioning
confidence: 99%